From triple-mode network to triple-layered model – novel insights in social cognition - Souvik Dubey; Samya Sengupta; Subhankar Chatterjee; Ritwik Ghosh; Siladitya Dewasi; Shambaditya Das; Alak Pandit; Mahua Jana Dubey (Indian Journal of Psychiatry)
Modern studies have revealed various pathophysiological mechanisms underlying neurodegenerative dementias. Among these, disruption of the “triple mode network” is widely recognized as a pivotal common pathway leading to the development of the neurodegenerative dementias including Alzheimer’s dementia. Contemporary studies have shown strong association of impaired social cognition with various dementias. However, how the misaligned social cognition leads to neurocognitive decline is still enigmatic. Herein, the authors introduce the term “triple-layered model of social cognition”, which encompasses the three pillars, that is, the basic “core cognitive constructs”, the value-based “higher-level cognitive constructs”, and instinct-driven “lower-level cognitive constructs (i.e., the bottom circuit)”. Dynamic interactions between the complex engrams of all three pillars form the “cogniverse”. The “higher-level cognitive constructs” may serve as a protective layer for the foundational “core cognitive constructs”, which are incessantly challenged by “the bottom circuit”. This could be a critical harbinger of neurocognitive decline. The authors further hypothesize that the derivatives of the miscalibrated social cognition, emerging from “the bottom circuit”, serve as “cognitive pollutants”. Here, authors introduce the term “social proteopathy” encompassing all social cognitive pollutants as a unified concept, which plays a significant pathological role in neurodegenerative dementias alongside biologically and genetically linked proteopathies. These social proteopathies have a profound deleterious impact on the “higher-level cognitive constructs” either through direct toxic potentials or via epigenetic modulation. Misdirected and maladaptive social cognition progressively erodes the layer of “higher-level cognitive constructs”, eventually having a deleterious impact on the fundamental “core cognitive constructs”, which, in turn, contribute to neurodegenerative dementias and various psychopathologies. The authors further attempt to classify “social brain” into six subtypes to assess the future “social cognitive debt” and the resulting aberrant behavioral burdens. Finally, the authors propose the way forward including genuine mindfulness-based practice and relentless exercise of the “higher-level cognitive constructs” in activities of daily living. This may act as a primordial preventive strategy against neurodegenerative dementias and various psychopathologies.